Optimalisasi Pokdarwis Massawi Melalui Tourism Service Management Pengembangan Objek Wisata Teluk Love Jember - Aryo Prakoso; Margaretta Andini Nugroho; Rebecha Prananta (Politeknik Negeri Cilacap, 2020)
Jember has a very diverse natural, cultural and artificial tourism potential. One of the natural potentials that currently become the prima donna in Jember is Teluk Love beach, located in Sumberrejo-Ambulu-Jember. The main attraction of the Love Bay is in terms of its shape that symbolizes love, which is not possessed by other destinations in Jember. The booming existence of the Love Bay increases tourist arrivals at this destination every day, in the other hand the condition of human resources and social economic environment is not ready to face of the growth of Love Bay tourism. Weak tourism knowledge, slum social environment patterns, society economic management are some challenges in developing this Love Bay tourism. Theoretically, if a tourist destination is well managed, tourists as subjects in the tourism industry have an important role in the sustainability of a tourist destination. The tourist services needs to get special attention. If the tourists are well served, then they will feel satisfied. This is a factor driving these tourists to come back, and with the more tourists it will have an effect on improving the economic level of the community itself. Based on the problems experienced by partners, the solutions that can be offered are providing soft skills training (attitude) for tourism services, providing hard skills training (procedural), providing assistance in the form of procurement of quality improvement service.